Competition Law and Policy Harmonisation: Its Relation to Fair Competition Realisation in ASEAN Single Aviation Market - A. A. B. N. A. Surya Putra (Udayana Journal of Law and Culture, 2019)
A well-functioning ASEAN Single Aviation Market Requires a level-playing field and fair competition. ASEAN does not have a multilateral agreement on competition related issues but opts to harmonise its Member States’ domestic legislation. This article asks whether this approach is appropriate to realise fair competition in ASEAN Single Aviation Market. It finds that mere harmonisation of laws and policies is insufficient without being complemented by effective implementation and enforcement. While regional enforcement is the ideal way of preventing and opposing unfair competition, this article also proposes the adoption of the concept of international comity as an achievable alternative to currently unequal ASEAN competition laws or the absence thereof.